2000
DOI: 10.1177/0016549200062002004
|View full text |Cite
|
Sign up to set email alerts
|

Media Use Habits, Audience Expectations and Media Effects in Hong Kong's First Legislative Council Election

Abstract: This research investigates the origin of audience expectations and their subsequent role in the media use-to-effects process. It argues that a significant portion of perceptions of media is couched in people's media habits and these perceptions in turn mediate political effects attributable to mass media. Contextualized in the first Legislative Council election in Hong Kong, our analysis of data from a survey of 503 local residents yielded several revelations. First, audience expectations of campaign media per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…But he did not take into account the fact that even today, although they are accessible and easy to use for virtually everybody, these media are still used for news and information in very different ways by different socio-economic groups in societies. Newspapers, for example, tend to be used more by those with higher SES who display not only stronger needs for serious and comprehensive news and information but also adequate cognitive resources to process it (Eijck and Rees 2000;Graber 1989;Guo 2000). In contrast, the universally accessible but more entertainment-orientated television medium, and other information services that require fewer cognitive skills, have been more associated with lower-SES groups (Atkin and LaRose 1994;Neuendorf et al 1998;Neuendorf et al 2002).…”
Section: Social Locatorsmentioning
confidence: 99%
“…But he did not take into account the fact that even today, although they are accessible and easy to use for virtually everybody, these media are still used for news and information in very different ways by different socio-economic groups in societies. Newspapers, for example, tend to be used more by those with higher SES who display not only stronger needs for serious and comprehensive news and information but also adequate cognitive resources to process it (Eijck and Rees 2000;Graber 1989;Guo 2000). In contrast, the universally accessible but more entertainment-orientated television medium, and other information services that require fewer cognitive skills, have been more associated with lower-SES groups (Atkin and LaRose 1994;Neuendorf et al 1998;Neuendorf et al 2002).…”
Section: Social Locatorsmentioning
confidence: 99%
“…Extradition bill opponents (who are anti-government) attributed to the journalists responsible the motive of defending the government, while supporters (who are pro-government) attributed the motive of advocating for personal positions on the issue. In the past, studies have found that audiences hold some general expectations about what journalists ought to do, such that Hong Kong adults expected news coverage to be comprehensive, objective, and positive during a national election campaign (Guo, 2000). Nonetheless, this study found that audiences also constantly assess journalistic roles as they read news, particularly thoughts about what the journalists responsible are trying to accomplish with their words.…”
Section: Discussionmentioning
confidence: 99%
“…According to Guo’s (2000) survey of 503 adults in Hong Kong, audiences expect journalists to provide comprehensive, objective, and positive news coverage during a national election campaign. In other words, news audiences do hold opinions regarding what journalists should do, and they also hold expectations of journalists’ roles (Tandoc and Duffy, 2016).…”
Section: Media Cynicismmentioning
confidence: 99%
“…The evaluation of the media thus reflects personal needs and interests, but at the same time it also overcomes them. People have certain shared normative expectations based on their perception of the media's role within the society, it seems, which cannot be explained simply by personal characteristics (Guo 2000).…”
Section: Audience Perspective and The Role Of Contextmentioning
confidence: 99%